A super-hydrophobic cotton fabric with excellent durability and its preparation method and application
By constructing a micro-nano-layered rough structure on the cotton cloth and introducing hydrophobic groups, the problem of easy destruction of the existing superhydrophobic materials is solved, and superhydrophobic cotton fabrics with excellent durability are prepared, which can achieve hydrophobic in practical applications. Sexual effect.
Patent Information
- Application Number
- CN202310252382.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-03-16
AI Technical Summary
The micro-nano-scale rough structures on the surface of existing superhydrophobic materials are easily damaged, thus losing their hydrophobicity, resulting in poor results in practical applications.
By constructing a micro-nano-layered rough structure on a cotton cloth, the polymer network structure formed by cross-linking reaction of dopamine and tannic acid, the deposition of SiO2 particles generated by TEOS hydrolysis and ZnO nanoparticles, combined with long-chain alkylsiloxanes The hydrophobic modifier introduces hydrophobic groups to prepare a superhydrophobic cotton fabric with excellent durability.
The prepared superhydrophobic cotton fabric remains superhydrophobic after being corroded by mechanical friction, strong acid, strong alkali, high salt and organic solvents, exhibits excellent durability, excellent self-cleaning, excellent oil-water separation performance and Sustainable use.
Smart Images

Figure CN116446180B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of super-hydrophobic materials, and in particular to a super-hydrophobic cotton fabric with excellent durability and a preparation method and application thereof. Background Art
[0002] With the continuous development of the global economy, the problem of offshore oil spills has become prominent, seriously endangering the marine ecological environment and threatening human life and health. Hydrophobic / oleophilic materials including sponges, foams, cotton fabrics, and hydrogels are considered to be the most promising materials for oil spill recovery. Among them, cotton fabrics, as a widely used natural material, have attracted extensive attention from scientific researchers due to their low price, easy availability, environmental friendliness, easy modification, and biodegradability.
[0003] Superhydrophobic / superoleophilic materials have attracted extensive attention from researchers because of their special surface wettability, which can achieve highly selective separation of a variety of immiscible oil-water mixtures. However, in practical applications, the micro-nanoscale rough structure on the surface of superhydrophobic materials is easily destroyed, thus losing their hydrophobicity. Therefore, although researchers have developed and prepared a large number of superhydrophobic materials for oil-water separation, there is still a long way to go before practical application. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a super-hydrophobic cotton fabric with excellent durability and a preparation method and application thereof, aiming to solve the problem that the micro-nano rough structure on the surface of the existing super-hydrophobic material is easily destroyed, thereby losing its hydrophobicity.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing a super-hydrophobic cotton fabric with excellent durability, comprising the steps of:
[0007] The cotton cloth is immersed in an alkali solution and etched to obtain an etched cotton cloth;
[0008] Prepare a first solution containing dopamine and tannic acid, take a tetraethyl silicate solution and mix it with the first solution to obtain a second solution, immerse the etched cotton cloth in the second solution to perform a first stirring reaction, and obtain a first intermediate product;
[0009] preparing a third solution containing ZnO, adding APTES to the third solution, performing a second stirring reaction, adding the first intermediate product to the system after the reaction, performing a third stirring reaction, and obtaining a second intermediate product;
[0010] The long-chain alkylsiloxane hydrophobic modifier solution is mixed with the second intermediate product, and a fourth stirring reaction is performed to obtain the super hydrophobic cotton fabric.
[0011] Optionally, the step of immersing the cotton cloth in an alkali solution for etching specifically comprises:
[0012] Wash and dry the cotton cloth;
[0013] The dried cotton cloth is immersed in alkali solution for etching, then rinsed with water and dried;
[0014] Wherein, the alkali solution is NaOH solution or KOH solution.
[0015] Optionally, the step of preparing a first solution containing dopamine and tannic acid, mixing a tetraethyl silicate solution with the first solution to obtain a second solution specifically comprises:
[0016] dissolving dopamine and tannic acid in a Tris-HCl solution to obtain a first solution containing dopamine and tannic acid;
[0017] Tetraethyl silicate is added to ethanol and mixed to obtain a tetraethyl silicate solution;
[0018] The tetraethyl silicate solution is added to the first solution to obtain a second solution.
[0019] Optionally, the step of preparing the third solution containing ZnO specifically includes:
[0020] ZnO is added to a mixed solution containing Tris-HCl buffer, water and ethanol to obtain a third solution containing ZnO.
[0021] Optionally, the cotton fabric is a nonwoven fabric, a cotton fabric or a fabric of a cellulose substrate;
[0022] The mass ratio of dopamine to tannic acid is 1:3-1:5;
[0023] The mass ratio of dopamine to tetraethyl silicate is 1:1-2:5.
[0024] Optionally, the conditions for the first stirring reaction are: reaction time is 8-12 hours, and reaction temperature is room temperature.
[0025] Optionally, the mass ratio of ZnO to APTES is 1:15-1:18;
[0026] The conditions of the third stirring reaction are: reaction time is 2h-4h, and reaction temperature is room temperature.
[0027] Optionally, the mass ratio of the long-chain alkylsiloxane hydrophobic modifier to the second intermediate product is 9:1-8:1;
[0028] The long-chain alkylsiloxane hydrophobic modifier is HDTMS.
[0029] A super hydrophobic cotton fabric with excellent durability, wherein the super hydrophobic cotton fabric is prepared by the preparation method according to the present invention.
[0030] The super hydrophobic cotton fabric with excellent durability as described in the present invention is used for oil-water separation.
[0031] Beneficial effects: The present invention forms a polymer network structure through the cross-linking reaction of tannic acid (TA) and dopamine (DA), and SiO 2 The deposition of ZnO nanoparticles and ZnO nanoparticles successfully constructed a micro-nano hierarchical rough structure on cotton, and then a long-chain alkylsiloxane hydrophobic modifier (such as HDTMS) was used to introduce hydrophobic groups, thereby obtaining a super-hydrophobic cotton fabric with excellent durability. The super-hydrophobic cotton fabric prepared by the present invention still has super-hydrophobicity (WCA>150°) after mechanical friction, strong acid, strong alkali, high salt, and organic solvent corrosion, showing excellent durability. Moreover, the super-hydrophobic cotton fabric not only has outstanding self-cleaning properties, but also has excellent oil-water separation performance and sustainable use and wide applicability. The development and design of the durable super-hydrophobic fabric is expected to be used to solve marine oil pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic flow chart of a method for preparing a super-hydrophobic cotton fabric with excellent durability in Example 1 of the present invention.
[0033] Figure 2 This is another schematic flow chart of a method for preparing a super-hydrophobic cotton fabric with excellent durability in Example 1 of the present invention.
[0034] Figure 3 In Example 1, CF (a 1 -a 2 )、CF-PDA / TA@SiO 2 (b 1 -b 2 ), CF@SiO 2 / ZnO (c 1 -c 2 ), CF@SiO 2 / ZnO-HDTMS (d 1 -d 2 ) SEM image of CF@SiO 2 / element spectrum of ZnO-HDTMS; (f) is the EDS image and relative percentage of element content.
[0035] Figure 4 In Example 1, CF, CF-PDA / TA@SiO 2CF@SiO 2 / ZnO and CF@SiO 2 XPS wide scan spectrum of CF@SiO / ZnO-HDTMS. (b) 2 C 1s spectrum of / ZnO-HDTMS.
[0036] Figure 5 In Example 1, (a) water droplets dyed with methyl orange and methyl blue were deposited on CF and CF@SiO 2 / ZnO-HDTMS, the inset is its static water contact angle (WCA) image; (b) CF and CF@SiO 2 / ZnO-HDTMS placed on the water surface; (c) A stream of water flows from CF@SiO 2 / ZnO-HDTMS surface rebound; (d) CF@SiO 2 / Underwater "silver mirror" phenomenon of ZnO-HDTMS. The inset is a schematic diagram of the Cassie-Baxter model.
[0037] Figure 6 In Example 1, (a) CF@SiO 2 Schematic diagram of wear resistance experiment of CF@SiO / ZnO-HDTMS. (b) 2 WCA of the friction side of CF@SiO / ZnO-HDTMS after 20 wear cycles on sandpapers with different mesh sizes. (c) and (d) are the WCA of the friction side of CF@SiO 2 The WCA of ZnO-HDTMS in aqueous solution or oil phase with different pH values changes with immersion time. The inset is the corresponding WCA.
[0038] Figure 7 In Example 1, (b) CF@SiO 2 Schematic diagram of the gravity-driven device for separating oil-water mixture using CF@SiO / ZnO-HDTMS. (c) 2 / ZnO-HDTMS separation efficiency of eight oil-water mixtures using a gravity-driven device. (d) CF@SiO 2 / ZnO-HDTMS separation efficiency of carbon tetrachloride / seawater mixture after different number of cycles using a gravity-driven device. The inset is the WCA image after different number of cycles.
[0039] Figure 8 In Example 1, (a 1 -a 6 ) CF@SiO 2 Schematic diagram of separation of oil-water mixture by peristaltic pump device. (b) CF@SiO 2 / ZnO-HDTMS separation efficiency of seven oil-water mixtures using a peristaltic pump device. (c) CF@SiO 2 / ZnO-HDTMS separation efficiency of n-hexane / seawater mixture after different cycles using a peristaltic pump. The inset shows the CF@SiO 2 Hydrophobicity image of / ZnO-HDTMS. DETAILED DESCRIPTION
[0040] The present invention provides a super-hydrophobic cotton fabric with excellent durability and a preparation method and application thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0041] Dopamine (DA) has excellent adhesion ability that is independent of the substrate, among which catechol groups and amino groups play a key role in the strong adhesion of polydopamine (PDA). The relatively cheap tannic acid (TA) with pyrogallol groups can undergo a cross-linking reaction with dopamine to form a composite coating. These methods are simple and green, the coating conditions are mild, and they can give the substrate surface a rough structure. Long-chain alkylsiloxane hydrophobic modifiers such as hexadecyltrimethoxysilane (HDTMS) are fluorine-free hydrophobic modifiers that can give the material excellent hydrophobicity. This embodiment introduces biomimetic adhesive coating and deposition of zinc oxide particles on cotton and modifies it with long-chain alkylsiloxane hydrophobic modifiers to prepare durable superhydrophobic cotton fabrics for oil-water separation.
[0042] Based on this, an embodiment of the present invention provides a method for preparing a super-hydrophobic cotton fabric with excellent durability, which comprises the steps of:
[0043] S10, immersing the cotton cloth in an alkali solution for etching to obtain an etched cotton cloth;
[0044] S20, preparing a first solution containing dopamine and tannic acid, mixing a tetraethyl silicate solution with the first solution to obtain a second solution, immersing the etched cotton cloth in the second solution to perform a first stirring reaction to obtain a first intermediate product;
[0045] S30, preparing a third solution containing ZnO, adding APTES to the third solution, performing a second stirring reaction, adding the first intermediate product to the system after the reaction, performing a third stirring reaction, and obtaining a second intermediate product;
[0046] S40, mixing a long-chain alkylsiloxane hydrophobic modifier solution (such as a HDTMS solution) with the second intermediate product, and performing a fourth stirring reaction to obtain the super-hydrophobic cotton fabric.
[0047] In this embodiment, the polymer network structure formed by the cross-linking reaction of TA and DA, the SiO 2 The deposition of ZnO particles and nano-ZnO particles successfully constructed a micro-nano hierarchical rough structure on cotton, and then a long-chain alkylsiloxane hydrophobic modifier (such as HDTMS) was used to introduce hydrophobic groups, thereby obtaining a super-hydrophobic cotton fabric with excellent durability. The prepared super-hydrophobic cotton fabric still has super-hydrophobicity (WCA>150°) after mechanical friction, strong acid, strong alkali, high salt, and organic solvent corrosion, showing excellent durability. Moreover, the super-hydrophobic cotton fabric not only has outstanding self-cleaning properties, but also has excellent oil-water separation performance and sustainable use and wide applicability. The development and design of this durable super-hydrophobic cotton fabric is expected to be used to solve marine oil pollution.
[0048] In step S10, in one embodiment, the step of etching the cotton cloth in an alkaline solution specifically includes:
[0049] Wash and dry the cotton cloth;
[0050] The dried cotton cloth is immersed in alkali solution for etching, then rinsed with water and dried;
[0051] The alkali solution is NaOH solution or KOH solution, but is not limited thereto.
[0052] In one embodiment, the step of etching the cotton cloth by immersing it in an alkali solution specifically comprises:
[0053] The cotton cloth was cleaned of surface impurities with deionized water and anhydrous ethanol in turn, dried and set aside. The dried cotton cloth was immersed in 50 mL NaOH solution (NaOH mass is 5 g) and etched for 20 min, then repeatedly rinsed with a large amount of deionized water and dried.
[0054] In step S20, in one embodiment, the step of preparing a first solution containing dopamine and tannic acid, mixing a tetraethyl silicate solution with the first solution to obtain a second solution specifically includes:
[0055] dissolving dopamine and tannic acid in a Tris-HCl solution to obtain a first solution containing dopamine and tannic acid;
[0056] Tetraethyl silicate is added to ethanol and mixed to obtain a tetraethyl silicate solution;
[0057] The tetraethyl silicate solution is added to the first solution to obtain a second solution.
[0058] In one embodiment, the mass ratio of dopamine to tannic acid is 1:3-1:5.
[0059] In one embodiment, the mass ratio of dopamine to tetraethyl silicate is 1:1-2:5.
[0060] In one embodiment, the conditions of the first stirring reaction are: reaction time is 8-12 hours, and reaction temperature is room temperature.
[0061] In one embodiment, the step of preparing a first solution containing dopamine and tannic acid, mixing a tetraethyl silicate solution with the first solution to obtain a second solution, and immersing the etched cotton cloth in the second solution for a first stirring reaction to obtain a first intermediate product specifically includes:
[0062] 0.2 g DA and 0.8 g TA were dissolved in 50 mL Tris-HCl solution (50 mM, pH = 8.5) to obtain a first solution containing dopamine and tannic acid. 500 μL TEOS was added to 5 mL ethanol and mixed evenly, then poured into the first solution to obtain a second solution. The etched cotton cloth was immersed in the second solution and stirred for 12 h at a stirring speed of 150 rpm. Then it was taken out, rinsed with deionized water, and dried at 80 ° C to obtain CF-PDA / TA@SiO 2 .
[0063] In step S30, in one embodiment, the step of preparing the third solution containing ZnO specifically includes:
[0064] ZnO is added to a mixed solution containing Tris-HCl buffer, water and ethanol to obtain a third solution containing ZnO.
[0065] In one embodiment, the mass ratio of ZnO to APTES is 1:15-1:18.
[0066] In one embodiment, the conditions of the third stirring reaction are: reaction time is 2h-4h, and reaction temperature is room temperature.
[0067] In one embodiment, the steps of preparing a third solution containing ZnO, adding APTES to the third solution, performing a second stirring reaction, adding the first intermediate product to the system after the reaction, performing a third stirring reaction, and obtaining the second intermediate product specifically include:
[0068] 0.15 g ZnO was added to 50 mL of mixed solution (the volume ratio of water to ethanol was 2:3, and 2.5 mL 1M Tris-HCl buffer with pH = 8.5 was added to the water), and then 3 mL APTES was added dropwise under stirring. The reaction was stirred at high speed for 2 h, and then CF-PDA / TA@SiO 2Immerse in the solution and react for 3 h. Take out and dry to obtain CF@SiO 2 / ZnO.
[0069] In step S40, in one embodiment, the step of mixing the HDTMS solution with the second intermediate product and performing a fourth stirring reaction to obtain the super-hydrophobic cotton fabric specifically includes:
[0070] 5 mL of HDTMS and 2 mL of deionized water were added to 50 mL of ethanol and the CF@SiO 2 / ZnO was immersed in the solution and stirred for 3 h, then taken out and dried at 80 °C after the ethanol evaporated to obtain CF@SiO 2 / ZnO-HDTMS.
[0071] The mechanism of forming super hydrophobic cotton fabric is further explained below.
[0072] In the weakly alkaline Tris-HCl buffer solution, the phenolic hydroxyl functional groups of the TA molecule are oxidized to quinone functional groups, and DA is oxidized by dissolved oxygen to self-polymerize to form oligomers. The amino groups of the oligomer PDA and the quinone functional groups of the TA molecule are cross-linked through Michael addition and Schiff base reaction in a weakly alkaline environment to form a polymer cross-linked network structure. The added TEOS is slightly soluble in water and hydrolyzes in water to form SiO 2 Nanospheres, and PDA has strong adhesion, which can stably adhere nanospheres to cotton to obtain CF-PDA / TA@SiO 2 After APTES is hydrolyzed in the third solution, it reacts with zinc oxide to fix it. In a weakly alkaline environment, the amino groups on the molecules react with the unreacted quinone functional groups in the TA molecules deposited on the cotton to undergo Michael addition and Schiff base reaction, thereby introducing nano zinc oxide onto the cotton to obtain CF@SiO 2 / ZnO, to achieve the construction of micro-nano hierarchical rough structure on cotton. HDTMS was used to introduce hydrophobic groups to modify the wettability of the above cotton fabric, and a super hydrophobic cotton fabric (i.e., CF@SiO 2 / ZnO-HDTMS).
[0073] In one embodiment, the cotton fabric may be, but is not limited to, a nonwoven fabric, and may also be selected from cotton fabric or a fabric of a cellulose substrate.
[0074] In one embodiment, the hydrolysis generates SiO 2 The reagent may be, but is not limited to, TEOS, and may also be selected from propyl orthosilicate.
[0075] In one embodiment, the long-chain alkylsiloxane superhydrophobic modifier may be but is not limited to HDTMS, and may also be selected from at least one of hexadecyltriethoxysilane, n-dodecyltrimethoxysilane, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and PDMS (polydimethylsiloxane).
[0076] The embodiment of the present invention further provides a super hydrophobic cotton fabric with excellent durability, wherein the super hydrophobic cotton fabric is prepared by the preparation method described in the embodiment of the present invention.
[0077] An embodiment of the present invention also provides an application of a super-hydrophobic cotton fabric with excellent durability, wherein the super-hydrophobic fabric prepared by the above preparation method is used for oil-water separation.
[0078] The present invention is further explained below by means of specific embodiments.
[0079] Example 1
[0080] Combination Figure 1-2 As shown, the method for preparing the super-hydrophobic cotton fabric with excellent durability of this embodiment comprises the following steps:
[0081] (1) Clean the impurities on the cotton cloth surface with deionized water and anhydrous ethanol in turn, dry it and set it aside. Immerse the dried cotton cloth in 50 mL NaOH solution (NaOH mass is 5 g) and etch it for 20 min, then rinse it repeatedly with a large amount of deionized water and dry it. Dissolve 0.2 g DA and 0.8 g TA in 50 mL Tris-HCl solution (50 mM, pH=8.5). Take 500 μL TEOS and add it to 5 mL ethanol, mix it evenly, and pour it into the above solution. Immerse the etched cotton cloth in the mixed solution and react it at 150 rpm for 12 h. Then take it out, rinse it with deionized water, and dry it at 80°C to obtain CF-PDA / TA@SiO 2 .
[0082] (2) 0.15 g ZnO was added to 50 mL of a mixed solution (the volume ratio of water to ethanol was 2:3, and 2.5 mL of 1 M Tris-HCl buffer, pH = 8.5, was added to the water). Then 3 mL of APTES was added dropwise under stirring. The reaction was stirred at high speed for 2 h. Then, CF-PDA / TA@SiO 2 Immerse in the solution and react for 3 h. Take out and dry to obtain CF@SiO 2 / ZnO.
[0083] (3) Add 5 mL of HDTMS and 2 mL of deionized water to 50 mL of ethanol and mix the CF@SiO 2 / ZnO was immersed in the solution and stirred for 3 h, then taken out and dried at 80 °C after the ethanol evaporated to obtain CF@SiO 2 / ZnO-HDTMS.
[0084] Comparative Example 1
[0085] This comparative example uses raw cotton as a comparative material, which is recorded as CF.
[0086] The cotton fabric (CF@SiO 2 / ZnO-HDTMS) and the cotton fabric (CF) prepared in comparative example 1 were used to separate the oil-water mixture using a gravity separation device. Carbon tetrachloride was selected as the oil phase.
[0087] The mixed solution of 50 mL carbon tetrachloride and 50 mL seawater was used as the oil-water mixture, and the oil-water separation test was carried out under the action of gravity using a separation device.
[0088] The efficiency of oil-water separation is given by the formula (m 0 Represents the mass of water before oil-water separation, m 1 represents the mass of water after oil-water separation).
[0089] It can be seen that under the same test conditions, the oil-water separation efficiency of the super-hydrophobic cotton fabric prepared in Example 1 can reach 99.3%, while the raw cotton prepared in Comparative Example 1 cannot achieve the effect of oil-water separation because it absorbs both water and oil.
[0090] The cotton fabrics prepared in Example 1 and Comparative Example 1 were subjected to separation tests on oil-water mixtures using a peristaltic pump device, wherein n-hexane was selected as the oil phase.
[0091] A mixed solution of 50 mL of n-hexane and 50 mL of seawater was used as the oil-water mixture, and an oil-water separation test was carried out with the assistance of a peristaltic pump device.
[0092] The dye degradation efficiency is given by the formula (W 0 , W 1 are the masses of the oil phase before and after separation by peristaltic pump assisted separation, respectively.
[0093] It can be seen that under the same test conditions, the oil-water separation efficiency of the super-hydrophobic cotton fabric prepared in Example 1 can reach 99.4%, while the raw cotton prepared in Comparative Example 1 cannot achieve the effect of oil-water separation because it absorbs both water and oil.
[0094] Figure 3 In Example 1, CF (a 1 -a 2 )、CF-PDA / TA@SiO 2 (b 1-b 2 ), CF@SiO 2 / ZnO (c 1 -c 2 ), CF@SiO 2 / ZnO-HDTMS (d 1 -d 2 ) Figure 3 (e) is CF@SiO 2 / Elemental spectrum of ZnO-HDTMS; Figure 3 (f) is CF@SiO 2 / EDS image of ZnO-HDTMS and relative percentage of element content.
[0095] Figure 4 In Example 1, (a) is CF, CF-PDA / TA@SiO 2 CF@SiO 2 / ZnO and CF@SiO 2 / XPS wide scan spectrum of ZnO-HDTMS; Figure 4 (b) is CF@SiO 2 C 1s spectrum of / ZnO-HDTMS.
[0096] Figure 5 In Example 1, (a) water droplets dyed with methyl orange and methyl blue were placed on CF and CF@SiO 2 / ZnO-HDTMS, the inset is its static water contact angle (WCA) image; (b) CF and CF@SiO 2 / ZnO-HDTMS placed on the water surface; (c) a stream of water flows from CF@SiO 2 / ZnO-HDTMS surface rebound; (d) CF@SiO 2 / Underwater "silver mirror" phenomenon of ZnO-HDTMS. The inset is a schematic diagram of the Cassie-Baxter model.
[0097] Figure 6 In Example 1, (a) CF@SiO 2 Schematic diagram of wear resistance experiment of CF@SiO / ZnO-HDTMS. (b) 2 WCA of the friction side of CF@SiO / ZnO-HDTMS after 20 wear cycles on sandpapers with different mesh sizes. (c) and (d) are the WCA of the friction side of CF@SiO 2 The WCA of ZnO-HDTMS in aqueous solution or oil phase with different pH values changes with immersion time. The inset is the corresponding WCA.
[0098] Figure 7In Example 1, (b) CF@SiO 2 Schematic diagram of the gravity-driven device for separating oil-water mixture using CF@SiO / ZnO-HDTMS. (c) 2 / ZnO-HDTMS separation efficiency of eight oil-water mixtures using a gravity-driven device. (d) CF@SiO 2 / ZnO-HDTMS separation efficiency of carbon tetrachloride / seawater mixture after different number of cycles using a gravity-driven device. The inset is the WCA image after different number of cycles.
[0099] Figure 8 In Example 1, (a 1 -a 6 ) CF@SiO 2 Schematic diagram of separation of oil-water mixture by peristaltic pump device. (b) CF@SiO 2 / ZnO-HDTMS separation efficiency of seven oil-water mixtures using a peristaltic pump device. (c) CF@SiO 2 / ZnO-HDTMS separation efficiency of n-hexane / seawater mixture after different cycles using a peristaltic pump. The inset shows the CF@SiO 2 Hydrophobicity image of / ZnO-HDTMS.
[0100] In summary, the super hydrophobic cotton fabric prepared by the present invention still has super hydrophobicity (WCA>150°) after mechanical friction, strong acid, strong alkali, high salt, and organic solvent corrosion, showing excellent durability. Moreover, the super hydrophobic cotton fabric not only has outstanding self-cleaning properties, but also has excellent oil-water separation performance and sustainable use and wide applicability. The development and design of the durable super hydrophobic fabric is expected to be used to solve marine oil pollution.
[0101] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a super-hydrophobic cotton fabric with excellent durability, characterized in that: Includes steps: The cotton cloth is immersed in an alkali solution and etched to obtain an etched cotton cloth; Prepare a first solution containing dopamine and tannic acid, take a tetraethyl silicate solution and mix it with the first solution to obtain a second solution, immerse the etched cotton cloth in the second solution to perform a first stirring reaction, and obtain a first intermediate product; preparing a third solution containing ZnO, adding APTES to the third solution, performing a second stirring reaction, adding the first intermediate product to the system after the reaction, performing a third stirring reaction, and obtaining a second intermediate product; Mixing the long-chain alkylsiloxane hydrophobic modifier solution with the second intermediate product, and performing a fourth stirring reaction to obtain the super-hydrophobic cotton fabric; The cotton fabric is a non-woven fabric, a cotton fabric or a fabric of a cellulose substrate; The mass ratio of dopamine to tannic acid is 1:3-1:5; The mass ratio of dopamine to tetraethyl silicate is 1:1-2:5; The mass ratio of ZnO to APTES is 1:15-1:18; The conditions of the third stirring reaction are: reaction time is 2h-4h, and reaction temperature is room temperature; The mass ratio of the long-chain alkylsiloxane hydrophobic modifier to the second intermediate product is 9:1-8:1; The long-chain alkylsiloxane hydrophobic modifier is HDTMS.
2. The preparation method according to claim 1, characterized in that: The step of immersing the cotton cloth in an alkali solution for etching specifically comprises: Wash and dry the cotton cloth; The dried cotton cloth is immersed in alkali solution for etching, then rinsed with water and dried; Wherein, the alkali solution is NaOH solution or KOH solution.
3. The preparation method according to claim 1, characterized in that: The step of preparing a first solution containing dopamine and tannic acid, mixing a tetraethyl silicate solution with the first solution to obtain a second solution specifically comprises: dissolving dopamine and tannic acid in a Tris-HCl solution to obtain a first solution containing dopamine and tannic acid; Tetraethyl silicate is added to ethanol and mixed to obtain a tetraethyl silicate solution; The tetraethyl silicate solution is added to the first solution to obtain a second solution.
4. The preparation method according to claim 1, characterized in that: The step of preparing the third solution containing ZnO specifically comprises: ZnO is added to a mixed solution containing Tris-HCl buffer, water and ethanol to obtain a third solution containing ZnO.
5. The preparation method according to claim 1, characterized in that: The conditions of the first stirring reaction are: reaction time is 8-12 hours, and reaction temperature is room temperature.
6. A super hydrophobic cotton fabric with excellent durability, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 5.
7. A method of using the super hydrophobic cotton fabric with excellent durability as claimed in claim 6 for oil-water separation.
Citation Information
Patent Citations
Preparation method of super-hydrophobic self-cleaning cotton fabric capable of being used for oil-water separation
CN114232342A
Cited By
Wear-resistant super-hydrophobic yarn with core-shell structure as well as preparation device and preparation method of wear-resistant super-hydrophobic yarn
CN122147686A